Garlic Mediated Green Synthesis of Silver Nanoparticles as Antifungal Agents against Magnaporthe oryzae - Bakhshi, Bahareh; Malla, Sudhakar; Gowda, Lokesh Siddalinge (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Plant elements such as carbohydrates, lipids, flavonoids, polyphenols, enzymes, terpenoids, and alkaloids are used as reducing substance in the green production of silver nanoparticles. The strategy proved to be highly straightforward, cost-effective, and practical. Materials and Methods: The synthesis of nanoparticles was validated using optical inspection, in which the yellow colour solution became brown. UV-visible spectroscopy, XRD, FTIR analysis, and SEM were used to further characterise the material. Results: Transmission electron microscopy have shown that the silver nanoparticles size was between 10–46 nm (SEM). Size of silver nanoparticles was found to be between 10–46nm approximately as determined by transmission electron microscopy (SEM). Well diffusion method demonstrated the antifungal activity of AgNPs on Magnaporthe oryzae with the zone of inhibition of 5 and 11mm when 12.5 and 25μg/ ml of AgNPs was used respectively. Lowest inhibitory concentration was found to be 5.2. Conclusion: The leakage of reducing sugars and proteins was used to explore the mode of action of nanoparticles’ antifungal activity, indicating that AgNPs were able to reduce membrane permeability
Keywords: Allium sativum; Magnaporthe oryzae; Silver nanoparticles; Conidia germination; inhibition assay; Colony growth inhibition assay